KAJIAN HUKUM TERHADAP PERLINDUNGAN KONSUMEN DALAM PENGGUNAAN PAYLATER TRAVELOKA - Dinnur Lutfi; Rika Lestari; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
PayLater is a form of P2P agreement which is a loan agreement from oneparty to another through a provider other than a bank, so there are other partiesinvolved in using the PayLater payment method. With the existence of otherparties, it is also possible to have various agreements in the use of the PayLatermethod, with the formation of an agreement between the parties, it can also beseen that the parties have an obligation to fulfill the achievements of other parties.In this case, the parties mentioned are consumers who also use PayLater on theirTraveloka account. So it can be said that the legal relationship that arisesbetween PayLater and consumers is when consumers use the payment methodowned by PayLater.This type of research can be classified in the type of normative legalresearch, which discloses laws and regulations relating to legal theories that arethe object of research. The approach taken is using a qualitative analysisapproach by searching for data in books, journals and other scientific worksrelated to this research. The data sources used are primary and secondary legalmaterials.The conclusions that can be drawn from the results of the research are:First, the regulation regarding the practice of using paylaters based on theprevailing laws and regulations in Indonesia is regulated in: Law Number 11 of2008 concerning Information and Electronic Transactions and PBI Number16/8/PBI/2014 concerning Amendment to Bank Indonesia Regulation Number11/12/PBI/2009 concerning Electronic Money (paylater position as electronicmoney or as a transaction tool at Traveloka) Second, Traveloka's liability ifconsumers are harmed by using paylaters, namely Traveloka is responsible forproviding protection to consumers, as regulated in the provisions of article 4 jo.Article 62 of Law Number 8 of 1999 concerning Consumer Protection and POJKNumber 1/POJK.07/2013 concerning Consumer Protection of the FinancialServices Sector.Keywords: Consumer Protection, PayLater, Traveloka, Legal Responsibility,Consumers.